Adsorption behaviour of SO2 and SOF2 gas on Rh-doped BNNT: a DFT study. (2nd January 2020) - Zhang, Xiaoxing; Chen, Zhenwei; Chen, Dachang; Cui, Hao; Tang, Ju
Abstract: As the insulating medium, SF6 is widely used in gas insulation equipment. Partial discharge and local overheating can cause the decomposition of SF6, resulting in a decrease in insulation strength of the equipment. The detection of SF6 decomposition gas can be used for on-line insulation detection of gas insulation equipment in electric power industry. In order to develop a new sensor gas sensing material for gas detecting. In this work, based on the first-principles density functional calculation (DFT) method of DMol 3, the adsorption of SF6 decomposition gas on (5, 0) Z-type Rh-BNNT in different ways was explored. The adsorption energy, adsorption distance, charge transfer as well as density of states were discussed. The results show that the adsorption strength between SO2 molecule with Rh-BNNT is larger than with SOF2 molecule, combined with desorption time, theoretically predicts Rh -BNNT have the potential to be a material for SO2 gas sensors. GRAPHICAL ABSTRACT: